2022
DOI: 10.3390/soilsystems6030058
|View full text |Cite
|
Sign up to set email alerts
|

Managing Sands of the Lower Mekong Basin to Limit Land Degradation: A Review of Properties and Limitations for Crop and Forage Production

Abstract: Land development is rapidly occurring on sand-dominant soils that cover substantial areas of the Lower Mekong Basin (LMB). Sands are at risk of degradation on sloping uplands where agriculture is expanding and on lowland landscapes where intensification of cropping is occurring. Sandstone and granitic geology explain the prevalence of sand-dominant textures of profiles in the LMB. However, the sand terrains in uplands of Cambodia and Southern Laos mostly have not been mapped in detail and the diversity of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The results of this study also showed that the application of a high rate of basal fertilizer, as in this study, was very inefficient and had the potential of nutrient leaching due to low soil CEC. Sandy soils with low CEC have a high potential for nutrient leaching [30].…”
Section: Effect Of Treatments On Nutrients Content In Plant Tissue An...mentioning
confidence: 99%
“…The results of this study also showed that the application of a high rate of basal fertilizer, as in this study, was very inefficient and had the potential of nutrient leaching due to low soil CEC. Sandy soils with low CEC have a high potential for nutrient leaching [30].…”
Section: Effect Of Treatments On Nutrients Content In Plant Tissue An...mentioning
confidence: 99%